Kepemimpinan Perempuan dan Transformasi Mutu Pendidikan di MAK Hamzanwadi II NW Lombok Timur - Aziz Al Amin Kutbi, L.M. Abdul; Acim, Subhan Abdullah; Fuadi, Abdulloh (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2025)
Women’s leadership in Islamic education plays a crucial role in transforming educational quality. This study explores how women’s leadership at MA Keagamaan (MAK) Hamzanwadi II NW Lombok Timur enhances learning outcomes through a rigorous selection system, integrated curriculum, and strong character-building approach. The institution accepts only 44 male and 44 female students annually, ensuring high-quality learners. The curriculum combines religious and general sciences, emphasizing Quranic recitation, Hadith memorization, classical Islamic texts (kitab kuning), and proficiency in Arabic and English. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews with school leaders, teachers, and students, as well as an analysis of institutional policies. Thematic analysis was applied to identify leadership patterns and their impact on educational excellence. Findings indicate that women’s leadership at MAK Hamzanwadi II NW Lombok Timur follows a transformational model, acting as facilitators, motivators, and innovators. Strategies include enhancing teacher competencies, integrating Islamic and modern knowledge, and reinforcing a disciplined academic culture. The school has achieved notable national and international academic successes, validating its commitment to excellence in education and student development. This study concludes that women’s leadership significantly contributes to shaping a competitive and character-driven learning environment, aligning with Islamization of Knowledge theory and ta’dib in Islamic education. Institutional support and gender-inclusive policies are essential to further strengthening women’s leadership in Islamic educational settings.